2020
DOI: 10.4236/jss.2020.81005
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Rules of Voting and Decision: A Literature Review

Abstract: Based on introducing the definition and some relative conceptions about voting and decision, this article focuses on presenting the factors that influence people's voting and decision making behaviors. Then several common voting rules and methods are summarized respectively. After introducing voting models, the application of voting and decision rules are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…These mobilizations are done by producing and airing or publishing political campaign messages to educate and influence voters to act during the elections. The author [2] also observed that, as Nigerians conducted their 2019 general elections, such political communication in various campaign messages was witnessed. He asserts, "Radio, which is one of the most frequent mediums used by campaign organizers and political parties, witnessed such presence of political campaign messages even higher".…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…These mobilizations are done by producing and airing or publishing political campaign messages to educate and influence voters to act during the elections. The author [2] also observed that, as Nigerians conducted their 2019 general elections, such political communication in various campaign messages was witnessed. He asserts, "Radio, which is one of the most frequent mediums used by campaign organizers and political parties, witnessed such presence of political campaign messages even higher".…”
Section: Introductionmentioning
confidence: 91%
“…A radio station needs to be independent, free and responsible to the public to create awareness for the citizens to know the problems and issues confronting the state and their possible solutions and consequences [9]. Voting is a political behaviour of choice or preference based on the information available to the voter [2]. The media's plan is always to sway the mass's opinion on a particular issue to achieve a specific result.…”
Section: Introductionmentioning
confidence: 99%
“…𝑖 𝑗 (4) being 𝑅 01 𝑖 𝑗 = {π‘˜ β‰  𝑖, 𝑗 | (π‘Ÿ π‘–π‘˜ , π‘Ÿ π‘˜ 𝑗 ) βˆ‰ 𝑅 01 }, 𝑅 01 = {(⟨1, 0⟩, ⟨0, 1⟩), (⟨0, 1⟩, ⟨1, 0⟩)}, and #𝑅 01 𝑖 𝑗 the cardinality of…”
Section: Consistencymentioning
confidence: 99%
“…Moving from an individual decision-maker to a group of them adds complexity to the decision-making process. For this reason, group decision-making models, such as voting-based models [4] or Delphi technique [5] , among others, have been developed. The problem is now longer choosing the appropriate course of action or option among several alternative possibilities by considering an individual' s opinion [6] , but rather the study must be extended to consider the difference of opinion or level of dissatisfaction among several parties [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Crisman (2014) uses representation theory of the symmetry group of the permutahedron to define an algebraic spectrum of voting rules connecting Borda to Kemeny. Other general overviews of ranked-choice voting are provided by Nurmi (2010) and Zhang (2020).…”
Section: Introductionmentioning
confidence: 99%